Cryopreservation of L929 cell culture in protective solutions containing hyaluronic acid - Seliuta, Anatolii; Smolyaninova, Yevgeniya; Kovalenko, Svitlana; Tymofieieva, Olena; Poliakova, Hanna; Gurina, Tetiana (Problems of Cryobiology and Cryomedicine, 2026)
Recently, cryobiological studies have focused on the prospects of using hyaluronic acid (HA) as a component of protective media during cryopreservation of various cell types. HA is a polysaccharide of natural origin and an integral component of the extracellular matrix, which determines its high biocompatibility and potential protective properties for cells under stressful conditions, in particular during freezing. The paper presents the results of cryopreservation of L929 cells using protective solutions containing 0.5% HA of various molecular weights as well as 5% of the classical endocellular cryoprotectant DMSO. Experimental protocols for the freezing of cells differed in the cryoprotective solution composition, the method of adding its components to cells, and the duration of cell exposure. The effectiveness of the cryopreservation protocols used was assessed by the viability of L929 cells and their adhesive properties. The results obtained showed that HA, regardless of its molecular weight, did not affect the penetration of DMSO through the membranes of L929 cells. The use of a cryoprotective solution containing only low-molecular-weight HA ensured cell survival at (72 ± 4.2) %, which did not differ from the values for the standard protocol. For high-molecular-weight HA, this index decreased to (42 ± 4.8) %. Regardless of the cryopreservation protocol, L929 cells retained the ability to attach to an adhesive surface. However, further growth and proliferation of cells largely depended on the composition of the cryoprotective solution and the conditions of administration of its components. Thus, it was shown that both low-molecular-weight HA and high-molecular-weight HA exhibited pronounced cryoprotective properties and can be used either as components of protective media in combination with DMSO, or as an independent impermeable cryoprotectant. Probl Cryobiol Cryomed. 2026; 36(1): 27—31